The mediating role of spiritual well-being and social support in the relationship between mental health and suicidal ideation among Malaysian university students - Ma’rof, Aini Azeqa; Abdullah, Haslinda; Azmi, Syasya Firzana (Human Resources Management Academic Research Society (HRMARS), 2024)
This study explores the mediating role of social support and spiritual well-being in the relationship between mental health and suicidal ideation among Malaysian university students. Utilizing a cross-sectional survey of 402 university students from various educational institutions across Malaysia, the research employs established instruments to measure the constructs. The findings indicate that mental health issues are significant predictors of suicidal ideation, with social support and spiritual well-being serving as crucial mediators. Students with better mental health who have strong social support networks and higher levels of spiritual well-being are less likely to experience suicidal ideation. This highlights the importance of fostering social support systems and enhancing spiritual wellbeing to mitigate the adverse effects of mental health issues. Practical strategies suggested include implementing peer support groups, mentorship programs, and spiritual well-being workshops to create a holistic approach to student mental health. In conclusion, the study provides empirical evidence on the mediating roles of social support and spiritual well-being in the relationship between mental health and suicidal ideation. By understanding these dynamics, mental health professionals and educational institutions can develop targeted strategies to support students in managing mental health issues, ultimately improving their overall well-being. These findings offer valuable insights for both academics and practitioners in mental health intervention and student support services.